2019
DOI: 10.3892/mmr.2019.10180
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin reverses doxorubicin resistance via inhibition the efflux function of ABCB4 in doxorubicin‑resistant breast cancer cells

Abstract: Doxorubicin is one of the most widely used chemotherapy agents for the treatment of breast cancer. However, the development of doxorubicin resistance limits the long-term treatment benefits in patients with breast cancer. Curcumin, a well-known dietary polyphenol derived from the rhizomes of turmeric ( Curcuma longa ), enhances the sensitivity of breast cancer cells to chemotherapeutic agents; however, the mechanisms underlying this phenomenon remain unclear. The aim of the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…When first discovered, ABCB4 was assumed to be a multi-drug exporter due to its high sequence conservation (76% identity, 86% similarity) to ABCB1 34 (P-glycoprotein), and ABCB4 is still often referred to as multidrug-resistance-protein 3 (MDR3). However, while various studies have shown ABCB4 to be capable of recognizing and transporting some ABCB1 substrates (albeit with low capacity) 35,36 , the data regarding its role in conferring drug resistance is inconclusive [37][38][39][40] . Similarly, ABCB1 has only been shown to flip short-chain, fluorescently labelled lipid analogues in cellular assays 41 , and despite its canalicular expression 3 , ABCB1 is unable to compensate for loss of ABCB4 function 1 .…”
mentioning
confidence: 99%
“…When first discovered, ABCB4 was assumed to be a multi-drug exporter due to its high sequence conservation (76% identity, 86% similarity) to ABCB1 34 (P-glycoprotein), and ABCB4 is still often referred to as multidrug-resistance-protein 3 (MDR3). However, while various studies have shown ABCB4 to be capable of recognizing and transporting some ABCB1 substrates (albeit with low capacity) 35,36 , the data regarding its role in conferring drug resistance is inconclusive [37][38][39][40] . Similarly, ABCB1 has only been shown to flip short-chain, fluorescently labelled lipid analogues in cellular assays 41 , and despite its canalicular expression 3 , ABCB1 is unable to compensate for loss of ABCB4 function 1 .…”
mentioning
confidence: 99%
“…Based on the reported data, polyphenols overcome multidrug resistance by affecting different pathways in different types of cancer [243]. For example: (i) quercetin increases apoptosis, inhibits angiogenesis (in colorectal cancer cells) [244], inhibits P-gp activity (in breast cancer cells) [245]; (ii) curcumin down-regulates P-gp and Hsp27, induces autophagy, reduces the markers of cancer stem cells (colon cancer cells) [246][247][248], inhibits the activity of ABCB4 pump, inhibits epithelial-mesenchymal transition (breast cancer cells) [249,250], inhibits JNK pathway, suppresses invasion by inhibition of STAT3 activity (prostate cancer) [251,252] or induces apoptosis (lung cancer cells) [253]; (iii) resveratrol down-regulates the expression of survivin (in prostate cancer cells) [254] and inhibits MAPK kinase in prostate and lung cancer cells [255]; (iv) EGCG inhibits drug efflux (in prostate cancer cells), increases drug concentration in cancer cells by inhibition of enzymes involved in drug metabolism (in colorectal cancer cells), increased ROS production (in colorectal cancer cells)-thus it is responsible for AMPK activation-and induces epigenetic restoration of estrogen receptors through histone modifications (in breast cancer cells) [256]. Nevertheless, based on reported data, some polyphenols can target the same molecule in different cancer cell lines.…”
Section: Synergic and Pleiotropic Activity Of Polyphenolsmentioning
confidence: 99%
“…Curcumin also inhibited the ATPase activity of ABCB4, without altering its protein expression, and slightly stimulated basal ATP hydrolysis by ABCB4 at low concentrations (0.25-1 µM). At higher concentrations, the activity of ATPase was inhibited [81]. In another study, in order to sensitize multidrug resistant breast cancer cells to cisplatin, MCF-7 and MCF-7/DDP cell lines were used.…”
Section: The Role Of Cur and Egcg In Reversing Multidrug Resistancementioning
confidence: 99%